Differences in health related quality of life among older migrants and nonmigrants in India - Vasim Ahamad; Ram B. Bhagat (Scientific Reports)
Abstract Increasing age with migration status might have a double risk of vulnerability to poor health outcomes. There is a lack of population-based studies on health-related quality of life (HRQoL) of older migrants in India. This study compares the HRQoL between older migrants and non-migrant populations in India and examines the role of migration-related factors. The Longitudinal Ageing Study in India (LASI) Wave-I data was used, and older persons aged 60 and above were selected for the study, which included 30,158 final samples. The HRQoL was measured based on a EuroQol Five-Dimension (EQ-5D) measure. The study used univariate and bivariate analysis to examine HRQoL differences between migrants and non-migrants, and logistic regression analysis was used to examine the association between HRQoL and migration status and other correlates of older persons. Over half of the older persons (55.9%) were growing older at destination places in India. The migrants showed a higher prevalence of poor HRQoL (44.5%) than non-migrants (34.8%). Further, the adjusted logistic regression result shows that migrants were likelier to have poor HRQoL [AOR 1.15; CI 1.09–1.22] than non-migrants. The migrants with 0–9 years of duration and migration at age 60 and above were significantly more likely to have poor HRQoL [AOR 1.20; CI 1.03–1.39] and [AOR 1.20; CI 1.04–1.39], respectively, than non-migrants. Moreover, the origin-destination place of migrants was also found to be significantly associated with poor HRQoL compared to non-migrants. The findings of our study reveal that persons with migration status had lower HRQoL than non-migrants. Some migration-related factors were significantly associated with HRQoL among migrants. However, this study predicts that migrants especially need separate health policies as they are in poorer health conditions than non-migrants. Policymakers should focus on the determinants of migrant health to achieve the goal of healthy ageing for all in India.